Elastoplastic analysis in functionally graded thick-walled rotating transversely isotropic cylinder under a radial temperature gradient and uniform pressure. (January 2021) - Temesgen, AG; Singh, SB; Pankaj, T
In this research paper, an analytical solution with numerical illustration is presented for elastoplastic analysis in a functionally graded thick-walled rotating transversely isotropic cylinder under a radial temperature gradient and uniform pressure using the transition theory of Seth and generalized strain measure theory. The theory of Seth requires no assumptions, such as infinitesimally small deformation or material incompressibility, or a yield criterion, and is important in determining elastoplastic transitional stresses and fully plastic stresses on the basis of Lebesgue strain measure. The combined impacts of an inhomogeneity parameter, uniform pressure, temperature, and angular speed are discussed numerically and shown graphically. It is concluded that a functionally graded thick-walled rotating cylinder made of steel subjected to a radial temperature gradient and uniform pressure is on safer than a cylinder made of titanium, owing to the percentage increase in pressure. This, in turn, brings to the concept of "stress saving, " which reduces the potential for thick-walled cylinder failure. The fully plastic circumferential stress with the application of thermal effects in a functionally graded cylinder is greater than that at room temperature on the inner surface, whereas fully plastic circumferential and radial stresses for a homogeneous cylinder are independent of thermal effects.